Alternatives in the management of osteoradionecrosis of the jaw: case report - Macias Angulo , Juan Pablo (2025)
Osteoradionecrosis is a devastating pathology because it affects the patient's quality of life, which is characterized by the presence of bone sequestration in an area that was previously exposed to oncological radiotherapy treatment. Currently there are different protocols as therapeutic alternatives; Hyperbaric oxygen therapy, the use of platelet-rich fibrin and tetracycline-induced fluorescence. Therefore, the objective of this report is to show a case of mandibular osteoradionecrosis where different therapeutic alternatives are used.